Comunicação do planejamento estratégico: um estudo de caso em uma indústria de bebidas - Brito, Iuri Gustavo (2006)
Orientated to the market, today exists a growing demand in managerial strategic communication in companies, and in their administration processes. Though, even with the use of the strategic planning, as administration tool, impediments exist in the moment of transmitting the planned strategies to the executioners, or to people directly related with them. In reason of this problem, the present study proposes a method for strategic planning communication, base of the whole structure of a business organization, once the established information among the different levels of decision makers, is directed to the construction, and accomplishment, of the intended vision for the company. To solve the narrated problem it was made a descriptive scientific research, with qualitative character, developed by a case study, including semi-structured interviews with managers responsible by different levels of decision makers in a soft drinks industry located in Santa Maria -Rio Grande do Sul.